Impact of antimetabolite discontinuation following cytomegalovirus or BK polyoma virus infection in kidney transplant recipients. Issue 6 (26th August 2022) - Dubrawka, Casey A.; Progar, Kristin J.; January, Spenser E.; Hagopian, Jennifer C.; Nesselhauf, Nicole M.; Malone, Andrew F.
Abstract: Background: Cytomegalovirus (CMV) and BK polyoma virus (BKV) infection following kidney transplantation have been associated with allograft dysfunction and allograft loss. Reduction in immunosuppression is a mainstay of management yet has been associated with increased risk of rejection. According to international consensus guidelines, one approach to management of these viral infections is to discontinue the antimetabolite. Little is known surrounding long‐term outcomes in these patients, and it remains unclear if consideration should be given to resuming the antimetabolite as variable re‐escalation strategies have been reported. The objective was to describe episodes of rejection and identify risk factors for rejection following antimetabolite withdrawal after CMV or BKV DNAemia in kidney transplant recipients. Methods: This single‐center, retrospective review evaluated adult kidney transplant recipients with a serum CMV or BKV DNA PCR ≥500 copies/ml who underwent antimetabolite discontinuation. The primary outcome assessed was the incidence of biopsy‐proven acute rejection (BPAR). Results: One hundred fifty‐nine patients were included. Overall, 14 patients (8.8%) experienced BPAR at a median of 1.6 years after antimetabolite discontinuation. Compared to CMV, discontinuation after BKV DNAemia was associated with a higher incidence of BPAR. Characteristics observed more frequently in patients with BPAR included younger age, female sex, higher initial viral load, and development of de novo donor‐specific antibody (DSA). Conclusion: These findings suggest that antimetabolite discontinuation after CMV or BKV DNAemia in kidney transplant recipients is a reasonable and safe approach. Further prospective studies investigating optimal immunosuppression management following CMV or BKV DNAemia in kidney transplant recipients are warranted. Abstract : Graphical abstract: